Call combinations in chimpanzees: a social tool?. (4th August 2022) - Leroux, Maël; Chandia, Bosco; Bosshard, Alexandra B; Zuberbühler, Klaus; Townsend, Simon W
Abstract: A growing body of evidence suggests the capacity for animals to combine calls into larger communicative structures is more common than previously assumed. Despite its cross-taxa prevalence, little is known regarding the evolutionary pressures driving such combinatorial abilities. One dominant hypothesis posits that social complexity and vocal complexity are linked, with changes in social structuring (e.g., group size) driving the emergence of ever-more complex vocal abilities, such as call sequencing. In this paper, we tested this hypothesis through investigating combinatoriality in the vocal system of the highly social chimpanzee. Specifically, we predicted combinatoriality to be more common in socially-driven contexts and in females and lower-ranked males (socially challenging contexts and socially challenged individuals respectively). Firstly, through applying methods from computational linguistics (i.e., collocation analyses), we built an objective repertoire of combinatorial structures in this species. Second, we investigated what potential factors influenced call combination production. We show that combinatoriality is predominant in 1) social contexts vs. non-social contexts, 2) females vs. males, and 3) negatively correlates with male rank. Together, these results suggest one function of combinatoriality in chimpanzees may be to help individuals navigate their dynamic social world. More generally, we argue these findings provide support for the hypothesized link between social and vocal complexity and can provide insight into the evolution of our own highly combinatorial communication system, language. Abstract : Recent attention within the field of ageing has focused on the relationship between the age of parents and the quality of offspring, but the picture that is emerging is that the presence of this aspect of ageing is highly variable. We describe a laboratory experiment that independently measured effects of maternal and paternal age effects on the fitness traits of larvae and female foster mothers in a species of insect that feeds its young during their development as larvae.